Molecular Epidemiology of Na+-Taurocholate Cotransporting Polypeptide Deficiency in Guangdong Province, China: A Pilot Study by Screening for Four Prevalent Variants of the Causative Gene SLC10A1 - Li, Hua; Chen, Rong; Lin, Gui-Zhi; Lin, Wei-Xia; Yaqub, Muhammad-Rauf; Song, Yuan-Zong (Frontiers in Genetics, 2022)
Na+-taurocholate cotransporting polypeptide deficiency (NTCPD) is an autosomal recessive disorder arising from biallelic SLC10A1 mutations. As a newly-described inborn error of bile acid metabolism, the epidemiology of this condition remains largely unclear in Chinese population so far. In this study, a total of 2828 peripheral blood samples were collected from 12 cities in Guangdong, a province with the largest population in China, and the four prevalent SLC10A1 variants c.800C>T (p.Ser267Phe), c.263T>C (p.Ile88Thr), c.595A>C (p.Ser199Arg) and c.665T>C (p.Leu222Ser) were screened for by using polymerase chain reaction (PCR)- restriction fragment length polymorphism (RFLP). As a result, 663 mutated SLC10A1 alleles were detected, and the mutated allele frequency was calculated to be 11.72% (663/5656), with a carrier frequency 20.69% (1/5) and a theoretical morbidity rate 1.37% (1/73) of NTCPD in Guangdong province. The variant c.800C>T(p.Ser267Phe) exhibited highest allele frequency among the four prevalent variants(2=1501.27, P<0.0001) as well as higher allele frequency in the peripheral region than that within the Pearl River Delta(2=4.834, P<0.05). The results suggested that NTCPD might be a disorder rather common in Guangdong province. The findings depicted the molecular epidemiologic features of NTCPD, providing preliminary but significant laboratory evidences for the subsequent NTCPD diagnosis and management in Guangdong population.